PENGARUH KEDWIBAHASAAN TERHADAP PENGUNAAN BAHASA SISWA DI SMA GEMBALA BAIK PONTIANAK - Willy, Willy; Saman, Sisilya; Patriantoro, Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe multiplicity of students colors the language usage of students in the school environment, especially in Pontianak Gembala Baik High School. Whereas in the use of language, Gembala Baik High School students are said to be bilingual because mastery of the first language and second language is equally good. The method used in this study is a descriptive method using SPEAKING analysis from Hymes. Of the 14 data, there are 36 words which are included in the field of language of phonology. In addition to the phonological level, there is also a clause at the semantic level, as well as mixed code out in the form of fragments of words, phrases, and clauses in English and Chinese. Whereas insertion in Chinese includes words, phrases and clauses. There is an event of code mixing in the form of inserting words in Javanese. Code switching is in phrases in English and Chinese as well as sentence code switching. And code switching in the field of phonology. Interference in the field of phonology, fields of morphology, interference in the field of syntax, and semantic field interference, as well as lexical field interference. There are 19 data visual integration, 7 data integration direct translation, and 2 integration concept translation.Keywords: code mixing, code switching, interference and integration